2016
DOI: 10.1371/journal.pone.0148711
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Activates a Neuregulin-Driven Circuit to Modify Surface Expression of Growth Factor Receptors of the ErbB Family

Abstract: Recently, the epidermal growth factor (EGF) receptor (EGFR), a member of the ErbB receptor family, and its down-stream signalling have been identified as co-factors for HCV entry and replication. Since EGFR also functions as a heterodimer with other ErbB receptor family members, the subject of the present study was to investigate a possible viral interference with these cellular components. By using genotype 1b replicon cells as well as an infection-based system we found that while transcript and protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Moreover, secreted HER3 has been shown to be a biomarker for early HCC in patients with chronic B hepatitis and cirrhosis [ 27 ]. By contrast, it has been recently demonstrated that HCV down-regulates HER3 expression at both transcript and protein levels in the Huh7 cell line [ 28 ]. Accordingly, we observed that HER3 mRNA levels were low in HCV-related HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, secreted HER3 has been shown to be a biomarker for early HCC in patients with chronic B hepatitis and cirrhosis [ 27 ]. By contrast, it has been recently demonstrated that HCV down-regulates HER3 expression at both transcript and protein levels in the Huh7 cell line [ 28 ]. Accordingly, we observed that HER3 mRNA levels were low in HCV-related HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ERBB2 was also targeted by pathogens for cellular entry 57 . The membrane association of EGFR and ERBB2 was increased during viral infection to benefit the processing of hepatitis C virus in previous studies 58,59 . Moreover, ERBB receptors are potent factors promoting cellular growth and survival, which could prolong host cell survival 60,61 and modulate host immune responses 62,63 to benefit viral production.…”
Section: Sars-cov-2 Fights Host Cell Immune and Antiviral Systemsmentioning
confidence: 84%
“…[ 53 ] HCV induces a substantial reduction of ErbB3 and ErbB4 expression. [ 54 , 55 ] DUSP1 regulates respiratory Syncytial virus and Sendai virus infection. [ 56 ] BACH1 knockdown reduces BZLF1 expression and further Epstein-Barr virus (EBV) infection.…”
Section: Discussionmentioning
confidence: 99%